Interactions between seagrasses and seaweeds during surge nitrogen acquisition determine interspecific competition - Alexandre, Ana (2018)
Seagrasses dominate shallow coastal environments where nitrogen (N) availability in the water column is often sporadic and mainly in the form of pulses. We investigated the N uptake competition between seagrasses and seaweeds through a series of N-15 surge uptake experiments combining single-species and mixed incubations across ammonium concentrations. N surge uptake rates of seagrasses were 2 to 14-fold higher than those of seaweeds in the majority of combinations, showing that seagrasses are generally in a competitive advantage over seaweeds in N-poor environments with N-pulses. No threshold concentration of ammonium was found beyond which seaweeds performed better than seagrasses. Mixed incubations revealed interspecific interactions that affected rates positively and negatively. Uptake rates obtained in single-species incubations, therefore, cannot always be used to predict the outcome of uptake competition. Only two (Zostera marina vs. Ulva rotundata and Zostera marina vs. Codium decorticatum) of the nine combinations tested (Z. marina, Z. noltei and Cymodocea nodosa vs. U. rotundata, C. decorticatum and Dictyota dichotoma) were found to enhance macroalgal uptake. Our results showed that the surge uptake capacity of seagrasses represents an important mechanism in their N acquisition strategy that justifies their dominance in shallow oligotrophic environments.